A revision of the Australian genus Pleuroseta Richards (Diptera, Sphaeroceridae) - Kuwahara, Gregory K.; Marshall, Stephen A. (European Journal of Taxonomy, 2023)
The Australian genus Pleuroseta Richards, 1973 is revised, including P. wentworthi (Richards, 1973) and three new species: P. ingens sp. nov. (Queensland), P. monteithi sp. nov. (Queensland) and P. occidentalis sp. nov. (Western Australia). Leptocera (Biroina) dorrigonis Richards, 1973 is treated as a new junior synonym of Pleuroseta wentworthi.